Bioinspired immobilization of carbon nanotubes on scaffolds for nerve regeneration. Issue 3 (2nd May 2019) - Nazeri, Niloofar; Tajerian, Roksana; Arabpour, Zohreh; Hadjighassem, Mahmoud Reza; Gheibi, Nematollah; Manouchehrabadi, Mahboubeh; Ghanbari, Hossein
Abstract : Carbon nanotubes (CNTs) have different applications in regenerative neurology such as neural signal transfer, nerve tissue engineering and neuroprosthetic devices. Their electrical conductivity and biocompatibility make them appropriate candidates for cell stimulation. This study was conducted to determine whether polydopamine (PD) can immobilize CNTs on the surface of nanofibrous scaffolds. To investigate this, electrospun scaffolds of poly(lactide- co -glycolide) (PLGA) were coated with CNTs both directly and by means of PD. Scanning electron microscopy (SEM), water contact angle measurement and Raman spectroscopy were used to verify the presence of dopamine on the surface of the scaffolds. The presence of PD on the substrate surface decreased the contact angle from 135·92 ± 2 to 82·65 ± 2°. Raman spectroscopy confirmed results by appearance of new peaks at 1350 and 1582 cm −1, which correspond to the aromatic component of PD. Measuring the electrical resistance proved that dopamine could effectively immobilize CNTs on the surface of nanofibers, decreasing the electrical resistance to 5·5 kΩ/square. Likewise, SEM images revealed a change in surface morphology induced by PD coating. Finally, cell viability studies demonstrated that CNT–PD–PLGA had no toxic effect on PC12 cells. The preliminary results were promising, supporting potential application of these materials as conductive scaffolds in nerve cell stimulation.